Oral Mucosa, Saliva, and COVID-19 Infection in Oral Health Care - Atukorallaya, Devi Sewvandini; Ratnayake, Ravindra K. (Frontiers in Medicine, 2021)
The SARS-CoV-2 virus has shaken the globe with an ongoing pandemic of COVID-19 and has set challenges to every corner of the modern health care setting. The oral cavity, oral mucosa and saliva are high risk sites for higher viral loads and dental health care professionals are considered a high risk group. COVID-19-induced oral lesions and loss of taste and smell are common clinical complaints in the dental health care setting. The SARS-CoV-2 virus has been found to cause a wide range of non-specific oral mucosal lesions, but the robust diagnosis of these lesions as COVID-19 lesions will aid in the prevention of SARS-CoV-2 in dental health care settings and proper patient management. The reported loss of taste and smell needs further investigation at the receptor level as it will give new insights into SARS-CoV-2 pathogenicity. The high yield of virus in the salivary secretion is a common finding in this infection and ongoing research is focusing on developing saliva as a rapid diagnostic fluid in COVID-19. In this brief review, we discuss the significance of oral mucosa and saliva and the relevance of the COVID-19 pandemic in dentistry.